Coronary angiography using second-generation dual source computed tomography: Feasibility of low dose and low flow rate to achieve appropriate individual contrast enhancement using a test bolus-based contrast medium protocol—A CONSORT compliant article. Issue 29 (July 2018) - Zhu, Xiaomei; Yu, Yusheng; Xu, Dinghu; Zhang, Hong; Tang, Lijun
Abstract : Abstract: Improved contrast enhancement consistency can be achieved using an individualized contrast media (CM) protocol. This study aimed to assess the feasibility of a low-dose, low-flow rate CM protocol to achieve appropriate individual contrast enhancement using a newly advocated individualized test bolus-based protocol for second-generation dual-source computed tomography angiography. CM containing iodine (370 mg I/mL) was used in this study. A CM flow rate of 3.5 mL/s for patients with a body mass index (BMI) <25.0 kg/m 2, and 4.5 mL/s for those with BMI ≥25.0 kg/m 2 was used in group 1 (n = 189). An individualized test-bolus based contrast injection protocol was then derived from the information gained from the test bolus and coronary enhancements in group 1. The proposed individualized test-bolus based CM injection protocol was applied in group 2 (n = 219). Ascending aortic attenuations (AAo) were measured and compared with both groups. The contrast enhancement consistency of AAo in group 2 improved significantly (31.8 vs 56.3 Hounsfield units [HU]; P  < .001). The number of patients in group 2 with a contrast flow rate ⩽3 mL/s was 63 (28.8%), with 77 (35.2%) using a contrast dose ⩽40 mL. In group 2, no significant differences in mean AAo were found among subgroups with contrast flow rates ⩽3.0, 3.1 to 4.0, 4.1 to 5.0 and >5.0 mL/s (351, 344, 346, and 348 HU, respectively), nor among subgroups with contrast doses ⩽40, 41 to 50, 51 to 60, and >60 mL (349, 345, 344, and 350 HU, respectively). Improved individual contrast enhancement uniformity can be achieved using an individualized CM protocol tailored to a test bolus. Approximately, one-third of patients received CM at a flow rate of no more than 3 mL/s and a total dose of no more than 40 mL.